Blood monocyte counts as a prognostic biomarker and predictor in Chinese patients with idiopathic pulmonary fibrosis - Zhang, Xinran; Ren, Yanhong; Xie, Bingbing; Ye, Qiao; Ban, Chenjun; Zhang, Shu; Zhu, Min; Liu, Yan; Wang, Shiyao; Geng, Jing; He, Xuan; Jiang, Dingyuan; et al. (Frontiers in Medicine, 2022)
Objectives We sought to evaluate the prognostic value of blood routine parameters and biochemical parameters, especially inflammation-related biomarkers, and establish an inflammation-related prognostic model in Chinese patients with idiopathic pulmonary fibrosis (IPF). Material/methods Patients diagnosed as IPF at Beijing Chaoyang Hospital and aged 40 years and older were consecutively enrolled from June 2000 to March 2015, and finally, a total of 377 patients were enrolled in the derivation cohort. The follow-up ended in December 2016. We used Cox proportional hazard model to calculate the hazard ratio (HR) and establish the prognostic model. The discrimination and calibration of the prognostic model were evaluated in an independent validation cohort enrolled from China-Japan Friendship Hospital between January 2015 and December 2019. Results Multivariate analysis revealed that patients with elevated monocyte-to-red blood cell count ratio (MRR) and monocyte counts showed increased risk of mortality. The clinical-physiological-biomarker (CPB) index and CPB stage we established in this study were a significant predictor, and the C-index for CPB index and CPB stage in the validation cohort was 0.635 (95% CI: 0.558–0.712) and 0.619 (95% CI: 0.544–0.694), respectively. Patients in CPB stage III had the poorest survival. Conclusion We developed and validated a new inflammation-related prognostic model (CPB index and CPB stage) which was integration of age, gender, FVC (%, predicted), DLCO (%, predicted), Charlson Comorbidity Index, and blood monocyte counts. This prediction model exhibited strong ability in predicting mortality in Chinese patients with IPF.